In vitro study on the antioxidant activity of methanolic leaf extract of Carica papaya - Aboobacker, Haseena K.; Valoth, Gopesh; Kizhedath, Sabeena (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Newer drug research worldwide is now focusing on medicinal plants for ensuring health and vitality due to the seemingly safer side effect profile and abundance of plants in nature, compared to synthetic drugs. Antioxidants are vital in preventing free radical induced tissue damage. The purpose of the present study is to evaluate the antioxidant activity of the methanolic extract of the leaves of Carica papaya using 1,1-diphenyl-2-picrylhydrazine (DPPH). Phytochemical tests proved the presence of bioactive ingredients in the extract. Methods: DPPH free radical assay, one of the most accurate methods for evaluating antioxidant activity, was used to evaluate the antioxidant activity of methanolic extract of leaves of C. papaya. Results: The methanolic leaf extract of C. papaya showed antioxidant property with free radical scavenging activity increasing with increase in concentration. The IC50 value of methanolic extract was 213.68 µgm/ml. Ascorbic acid was used as control. Conclusions: Oxidative stress has been linked to heart disease, cancer, immune deficiency. Antioxidants as suggested from various studies may reduce the risk of such diseases. The utility of C. papaya in the treatment of heart disease, cancer and immune deficiency will have to be proved by detailed evaluation of its pharmacological properties.